Corpo e Spazio: Husserl, Merleau-Ponty, Lacan - Moroncini, Bruno (Bollettino Filosofico, 2018)
Starting from the analysis of the body in the phenomenological tradition, and by means of the mediation of Merleau-Ponty’s thought, the essay aims to address the Lacanian theorization of the body as a pulsional body, in which the phenomenological centrality of vision is traced back to the specific performance of the scopic pulsion. The essay will be divided into three parts. The first one will reconstruct the Husserlian theorization of the theme of the proper body (Leib) or living body, mainly from Ideas II, the lessons on passive synthesis, and those on the Crisis of European Sciences, in which the concept of “world of life” is put at stake. In the second part, after a few words on the Gestalt-psychology, the production of Maurice Merleau-Ponty will be analyzed starting from the Phenomenology of perception, passing through the Lessons on child psychology held at the Sorbonne in 1949 – in which the relationship with Lacan and more specifically with his writing on the mirror stage is already present –, until the thesis on the flesh and the relationship between “seeing” and “being seen” in The Visible and the Invisible. Finally, in the third part, I will analyze Lacan’s conferences on Merleau-Ponty, and the section of the seminar on the four fundamental concepts of psychoanalysis entitled The gaze as object a, in which the scopic pulsion is discussed.